Reflecting on a collaborative approach to a regional sustainability transition: Dingle Peninsula 2030. Issue 3 (4th May 2021) - Boyle, Evan; Watson, Clare; McGookin, Connor; Deane, Aoife; de Bhailís, Deirdre; McElligott, Claire; O'Hara, Seamus; Tuohy, Brendan; Mullally, Gerard; Gallachóir, Brian Ó
ABSTRACT: This paper uses a reflective method to gather findings with relation to a collaborative governance approach for the sociotechnical transition to a low carbon society in a regional context. As top-down and bottom-up approaches to sustainable transitions have proven insufficient in bringing about the necessary changes required to meet the demands of climate action, more collaborative approaches between local communities, national public bodies and research organisations are warranted. Within this, there is a need to understand the dynamics of collaborative governance for participants in the process. Through a process of reflective practice, this paper outlines the networks, personal capacities, organisational capacities, benefits and challenges of collaborative governance partnerships for sustainable transitions from the perspective of individuals within a collaborative committee working on a regional transition project on the Dingle Peninsula, Co Kerry, Ireland. Alongside this, some solutions to challenges outlined through reflection are highlighted. This research paper highlights the need for the incorporation of reflective practice within collaborative governance for the socio-technical transition to a low-carbon society.